Peran Purchasing dalam Menunjang Pengadaan Bahan Makanan untuk Operasional Kitchen di Padma Resort Legian (International Forum of Researchers and Lecturers, 2025)
Purchasing plays a role in ensuring the availability of food ingredients with good quality and efficient costs, managing risks, supporting product innovation, and increasing efficiency in the food procurement process, with such an important role the hotel industry continues to strive to improve purchasing capabilities and competencies in order to be better in the food procurement process. Purchasing together with its duties and sections must understand and know and organize food procurement activities with clearly coordinated concepts and planning patterns and satisfactory and responsive services in any situation faced by both fellow employees and hotel guests. This type of research is descriptive qualitative with a Phenomenological approach. In this study, an interview method was used with 4 informants who were purchasing officers and receiving at Padma Resort Legian. This study aims to determine the role of purchasing in supporting the need for food procurement for kitchen operations at Padma Resort Legian. From the interview results, it can be concluded that the procurement of food ingredients for kitchen operations at Padma Resort Legian, which includes processing purchase requests, selecting suppliers, giving instructions to suppliers and receiving food ingredients, has been carried out correctly and in accordance with the Standard Operating Procedures (SOP) at Padma Resort Legian. Supplier selection has also been carried out in accordance with the Standard Operating Procedures (SOP) at Padma Resort Legian, but purchasing must be more careful in selecting and determining suppliers to avoid inconsistent delivery of food ingredients in terms of time, quantity, and quality of the food ingredients.